Orthogonal crystal phase Nb18V4O55 electrochromic film as well as preparation method and application thereof
The preparation of orthogonal crystal phase Nb18V4O55 electrochromic film through magnetron sputtering and annealing treatment solves the problem of difficult to achieve the 'warm state' mode in the prior art, realizes efficient electrochromic dual-band regulation, and has fast response and high stability characteristics.
Patent Information
- Application Number
- CN202411370574.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-29
AI Technical Summary
Existing single-component dual-band electrochromic materials are difficult to achieve the ‘warm state’ mode, and the method of achieving the ‘warm state’ mode is complex and has high preparation cost.
The metal Nb and metal V were co-sputtered on the substrate surface by magnetron sputtering method to obtain an amorphous Nb18V4O55 film, and an annealing treatment was used to form an orthogonal crystal phase Nb18V4O55 electrochromic film.
The ‘warm state’ mode of electrochromic dual-band regulation through the intrinsic properties of the material is realized, with excellent electrochromic ability, fast kinetic response and high cycling stability.
Smart Images

Figure CN119392167A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochromic technology, in particular to an orthorhombic phase Nb 18 V 4 O 55 Electrochromic film and its preparation method and application. Background Art
[0002] Electrochromism refers to the phenomenon that under the action of an external electric field, cations and electrons in an electrolyte are reversibly injected or extracted from a material under the drive of an electric field, causing a redox reaction inside the material, thereby causing a reversible change in the optical properties of the material. At present, the earliest and most widely used application of electrochromism is smart windows. The electrochromic layer of smart windows has adjustable optical transmittance under the action of an electric field, which can achieve the regulation of indoor lighting and thermal radiation, reduce the energy consumption required for heating, cooling, and lighting in buildings, and also improve indoor natural lighting, which is expected to alleviate the worsening urban light pollution problem in contemporary times.
[0003] At present, most electrochromic materials are concentrated in the visible light band for regulation, while the energy of sunlight is mainly concentrated in the visible light and near-infrared bands, of which visible light and near-infrared each account for nearly 50%. Therefore, the development of electrochromic materials that can independently control the transmittance of visible light and near-infrared is of great significance for the widespread application of electrochromic materials.
[0004] The use of dual-band electrochromic materials in smart windows is expected to achieve four adjustment modes: "bright state", "dark state", "warm state" and "cold state". "Bright state" means that the film is transparent, that is, it maintains high transmittance in both the visible light band and the near-infrared band; "dark state" means that the transmittance of both visible light and near-infrared light is low or even completely non-transmitted; "warm state" means that the transmittance of the near-infrared band is high and the transmittance of the visible light band is low; "cold state" means that the transmittance of the visible light band is high and the transmittance of the near-infrared band is low.
[0005] Although there have been a lot of studies in this field, dual-band electrochromic materials can only achieve the sequential switching of "bright state", "cold state" and "dark state" modes, while materials that achieve the "warm state" mode are rarely reported. In current reports, the "warm state" mode is usually achieved by using cathode and anode composite electrochromic materials or by combining the performance of the counter electrode into a device; or by adjusting the electrolyte or combining electrochromism with other technologies. It is worth noting that it is difficult to achieve the "warm state" mode using only single-component dual-band electrochromic materials, and in the current reports on the realization of the "warm state" mode, the complex preparation and high preparation cost limit its large-scale application in smart windows. In addition, not only "warm state" materials and devices, but all dual-band electrochromic materials and devices still face problems such as poor performance, interface contact, and poor cycle stability. In general, although researchers have made great progress in the field of dual-band electrochromism by optimizing material composition and device structure, there are still many key issues that need to be solved to promote its future research and wide application, especially the development of "warm state" materials and devices.
[0006] Therefore, more new electrochromic materials are yet to be discovered, and existing technologies are yet to be improved and developed. Summary of the invention
[0007] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide an orthorhombic phase Nb 18 V 4 O 55 The electrochromic film and its preparation method and application are aimed at solving the problems that the existing single-component dual-band electrochromic materials are difficult to achieve the "warm state" mode, and the current methods for achieving the "warm state" mode are complex and the preparation cost is high.
[0008] The technical solution of the present invention is as follows:
[0009] In a first aspect of the present invention, there is provided an orthorhombic phase Nb 18 V 4 O 55 Application of materials in electrochromic films.
[0010] In a second aspect of the present invention, there is provided an orthorhombic phase Nb 18 V 4 O 55 A method for preparing an electrochromic film, comprising the steps of:
[0011] The magnetron sputtering method is used to co-sputter metal Nb and metal V on the substrate surface to obtain amorphous Nb on the substrate surface. 18 V 4 O 55 film;
[0012] For the amorphous Nb 18 V 4 O 55 The film was annealed to obtain orthorhombic Nb 18 V 4 O 55 Electrochromic film.
[0013] Optionally, in the magnetron sputtering method, a metal niobium target and a metal vanadium target are used to co-sputter metal Nb and metal V on the substrate surface, wherein the power supply power of the metal niobium target is 100W to 200W, and the power supply power of the metal vanadium target is 25W to 125W.
[0014] Optionally, the metal niobium target and the metal vanadium target co-sputter metal Nb and metal V on the substrate surface in a molar ratio of 1:0.2 to 0.45.
[0015] Optionally, the distance between the center position of the surface of the metal niobium target and the metal vanadium target and the center position of the surface of the substrate is 120 mm to 150 mm.
[0016] Optionally, the working gas of the magnetron sputtering method is oxygen and argon, wherein the ratio of oxygen to argon is 5 sccm:45 sccm, and the gas pressure is 1 Pa to 1.5 Pa.
[0017] Optionally, in the annealing treatment, the annealing temperature is 550° C. to 650° C., and the annealing time is 120 min to 300 min.
[0018] A third aspect of the present invention provides an orthorhombic phase Nb 18 V 4 O 55 The electrochromic film, wherein the orthorhombic phase Nb 18 V 4 O 55 The electrochromic film is prepared by a preparation method.
[0019] Optionally, the orthorhombic phase Nb 18 V 4 O 55 The thickness of the electrochromic film is 300nm to 350nm.
[0020] In a fourth aspect of the present invention, an electrochromic device is provided, comprising a transparent conductive layer, an electrochromic layer, an electrolyte layer and an ion storage layer, wherein the electrochromic layer comprises the orthorhombic phase Nb 18 V 4 O 55 Electrochromic film.
[0021] Beneficial effect: The present invention discloses orthorhombic phase Nb 18 V4 O 55 The application of materials in electrochromic films, and the orthorhombic phase Nb was successfully prepared by magnetron sputtering combined with annealing method. 18 V 4 O 55 The electrochromic film is simple and low-cost. The prepared orthorhombic phase Nb 18 V 4 O 55 The electrochromic film not only has excellent electrochromic ability, but also can realize the "warm state" mode of electrochromic dual-band regulation with the intrinsic properties of the material. At the same time, it has a large optical modulation amplitude. The electrochromic film also has the characteristics of fast kinetic response and high cyclic stability. These characteristics make it have the potential for commercial application in smart windows, display devices and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The orthorhombic phase Nb prepared in Example 1-6 18 V 4 O 55 Comparison of XRD diffraction pattern of electrochromic film and PDF standard card.
[0023] Figure 2 Orthorhombic Nb 18 V 4 O 55 A graph showing the full-band optical transmittance changes of electrochromic film at different voltages during the electrochromic process.
[0024] Figure 3 Orthorhombic Nb 18 V 4 O 55 A graph showing the change in single-wavelength optical transmittance of an electrochromic film over time during the electrochromic process.
[0025] Figure 4 Orthorhombic Nb at different scanning rates 18 V 4 O 55 Single-wavelength optical transmittance variation of electrochromic films.
[0026] Figure 5 Orthorhombic Nb 18 V 4 O 55 Single-wavelength optical transmittance variation of electrochromic film during cyclic stability test. DETAILED DESCRIPTION
[0027] The present invention provides an electrochromic film and a preparation method and application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0028] The embodiment of the present invention provides an orthorhombic phase Nb 18 V 4 O 55 Application of materials in electrochromic films.
[0029] The embodiment of the present invention discloses orthorhombic phase Nb 18 V 4 O 55 Application of materials in electrochromic films, prior art on orthorhombic phase Nb 18 V 4 O 55 The research on materials is mainly focused on the fields of electrocatalysis and batteries, and there has been no report on electrochromism. 18 V 4 O 55 The material is used in electrochromic thin films to obtain orthorhombic phase Nb 18 V 4 O 55 The electrochromic film not only has excellent electrochromic ability and strong optical modulation ability, such as about 70% modulation ability in the visible light band (550nm) and about 85% modulation ability in the near infrared band (1100nm); it can also realize the "warm state" mode of electrochromic dual-band regulation, that is, the transmittance of the visible light band can be reduced first while the transmittance of the near infrared band remains unchanged, and as the voltage continues to decrease, it is expanded to the decrease of the entire visible light and near infrared. And it realizes this "warm state" regulation mode by utilizing the intrinsic properties of the material on the inorganic oxide electrochromic material, without relying on the design of the material microstructure, composition or device. In addition, the orthorhombic phase Nb 18 V 4 O 55 Electrochromic films also have the characteristics of fast kinetic response and high cycle stability, which make orthorhombic Nb 18 V 4 O 55 The film has the potential for commercial applications in areas such as smart windows and display devices.
[0030] The embodiment of the present invention also provides an orthorhombic phase Nb 18 V 4 O 55 A method for preparing an electrochromic film, comprising the steps of:
[0031] S1. Co-sputtering metal Nb and metal V on the substrate surface by magnetron sputtering method to obtain amorphous Nb on the substrate surface. 18 V 4 O 55 film;
[0032] S2, the amorphous Nb 18 V 4 O 55 The film was annealed to obtain orthorhombic Nb 18 V 4 O 55 Electrochromic film.
[0033] The present invention innovatively uses a magnetron sputtering method combined with an annealing method to successfully prepare the orthorhombic phase Nb 18 V 4 O 55 Compared with the traditional chemical synthesis method, the electrochromic film prepared by the method of the present invention is simple to operate, and the electrochromic film not only has excellent electrochromic performance and strong optical modulation ability, but also has an electrochromic "warm state" adjustment mode.
[0034] The orthorhombic phase Nb in the embodiment of the present invention 18 V 4 O 55 The electrochromic film is prepared by magnetron sputtering deposition combined with post-annealing, wherein the steps of magnetron sputtering and annealing can be completed separately, or can be obtained by magnetron sputtering combined with in-situ heating annealing.
[0035] In some embodiments, in the magnetron sputtering method, a metal niobium target and a metal vanadium target are used to co-sputter metal Nb and metal V on the surface of a substrate, wherein the power of the metal niobium target is 100W to 200W (for example, 100W, 110W, 120W, 130W, 140W, 150W, 160W, 170W, 180W, 190W, 200W), the power of the metal vanadium target is 25W to 125W (for example, 25W, 35W, 45W, 55W, 65W, 75W, 85W, 95W, 105W, 115W, 125W), and the distance between the center position of the surface of the metal niobium target and the center position of the surface of the substrate is 120mm to 150mm (for example, 120mm, 125mm, 130mm, 135mm, 140mm, 145mm, 150mm).
[0036] In this embodiment, the power of the metal niobium target and the metal vanadium target is set within the above range, and amorphous Nb can be obtained by sputtering metal niobium and metal vanadium in a suitable mixing ratio on the substrate surface. 18 V 4 O55 The film can be annealed to obtain orthorhombic phase Nb 18 V 4 O 55 Electrochromic thin film. Setting the relative positions of the metal niobium target and the metal vanadium target to the substrate within the above range is conducive to making the composition of the thin film obtained by magnetron sputtering uniform.
[0037] In some embodiments, the magnetron sputtering method uses a metal niobium target and a metal vanadium target to co-sputter metal Nb and metal V on the substrate surface in a molar ratio of 1:0.2 to 0.45, for example, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4 or 1:0.45. Within this molar ratio range, the amorphous Nb 18 V 4 O 55 After annealing, the films can form the same orthorhombic crystal structure, and finally the orthorhombic phase Nb 18 V 4 O 555 Electrochromic film can achieve excellent electrochromic ability.
[0038] In some embodiments, the orthorhombic phase Nb 18 V 4 O 555 The electrochromic film may also include doping elements, wherein the doping elements are selected from one or more of tungsten, titanium, nickel, and molybdenum. Since the doping ratio of the doping elements is very small, the Nb 18 V 4 O 55 The original crystal structure of the material, the electrochromic film can still have good electrochromic ability. For example, the orthorhombic phase Nb 18 V 4 O 555 The electrochromic film may include a tungsten doping element, in which case the chemical formula of the material contained in the electrochromic film becomes Nb 18 W x V 4 O 55 (where x is 0 to 2), but the material will still retain the original Nb 18 V 4 O 55 The crystal structure of the orthorhombic phase of a material.
[0039] In some embodiments, the working gas of the magnetron sputtering method is oxygen and argon, wherein the ratio of oxygen to argon is 5 sccm:45 sccm, and the gas pressure is 1Pa-1.5Pa. If necessary, the oxygen flow rate can be appropriately increased according to the situation. The relatively high oxygen flow rate will not cause the amorphous Nb 18 V 4O 55 The material is in an oxygen-deficient state, so the oxygen flow rate needs to be regulated. And the adjustment of air pressure usually affects the density of the material. When adjusted within an appropriate range, lower air pressure will make the material denser and usually have better electrochromic performance.
[0040] In some embodiments, in the annealing treatment, the annealing temperature is 550°C to 650°C (for example, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C), and the annealing time is 120min to 300min (for example, 120min, 150min, 200min, 250min, 300min). When the material is annealed under this parameter, the material will not crystallize into other crystalline phases due to too high a temperature, and the appropriate annealing time allows the material to achieve the best crystallinity.
[0041] The embodiment of the present invention also provides an orthorhombic phase Nb 18 V 4 O 55 The electrochromic film, wherein the orthorhombic phase Nb 18 V 4 O 55 The electrochromic film is prepared by the preparation method.
[0042] The orthorhombic phase Nb provided by the present invention 18 V 4 O 55 The electrochromic film not only has excellent electrochromic ability and strong optical modulation ability, but also can realize the "warm state" mode of electrochromic dual-band regulation. In addition, it also has the characteristics of fast kinetic response and high cycle stability. These characteristics make the orthorhombic phase Nb 18 V 4 O 55 Electrochromic films have the potential for commercial applications in areas such as smart windows and display devices.
[0043] In some embodiments, the orthorhombic phase Nb 18 V 4 O 55 The thickness of the electrochromic film is 300 nm to 350 nm. Within this thickness range, the film has both large optical modulation capability and response speed.
[0044] The present invention also provides an electrochromic device, which comprises a transparent conductive layer, an electrochromic layer, an electrolyte layer and an ion storage layer, wherein the electrochromic layer comprises the orthorhombic phase Nb 18 V 4 O55 Electrochromic film.
[0045] The present invention will be further described below by means of specific examples.
[0046] Example 1
[0047] This embodiment provides an orthorhombic phase Nb 18 V 4 O 55 The electrochromic film and the preparation method thereof are as follows:
[0048] Amorphous Nb was deposited by co-sputtering metal Nb and metal V on ITO quartz glass using magnetron sputtering. 18 V 4 O 55 Thin film, oxygen and argon are introduced into the magnetron sputtering chamber during film deposition, the ratio of oxygen and argon is 5sccm:45sccm, and the gas pressure is about 1.2Pa. Metal niobium target and metal vanadium target are used as target materials, and a DC sputtering power supply is used. The power of the metal niobium target is 150W, and the power of the metal vanadium target is 76W. The metal niobium target and the metal vanadium target co-sputter the metal Nb and metal V on the surface of ITO quartz glass with a molar ratio of 1:0.25. During the deposition process, the sample stage is rotated to maintain the element ratio and thickness of the film uniformly, and the distance between the surface center position of the metal niobium target and the surface center position of the substrate is kept at 150mm. Amorphous Nb deposited by magnetron sputtering 18 V 4 O 55 The film appears as a light yellow transparent film.
[0049] The amorphous Nb deposited by magnetron sputtering 18 V 4 O 55 The film was placed in a muffle furnace for high temperature annealing treatment. The temperature was first raised from room temperature to 600°C in 60 minutes, then kept at 600°C for 120 minutes, and finally cooled naturally to room temperature. The annealing process was carried out in an atmospheric environment to obtain orthorhombic Nb 18 V 4 O 55 Electrochromic film.
[0050] Example 2
[0051] The preparation method of Example 2 is the same as that of Example 1, except that the power of the metal vanadium target is adjusted to 67W, wherein the metal niobium target and the metal vanadium target are co-sputtered on the surface of the ITO quartz glass with a molar ratio of metal Nb and metal V of 1:0.2. 18 V 4 O55 Electrochromic film.
[0052] Example 3
[0053] The preparation method of Example 3 is the same as that of Example 1, except that the power of the metal vanadium target is adjusted to 85W, wherein the metal niobium target and the metal vanadium target are co-sputtered on the surface of the ITO quartz glass with a molar ratio of metal Nb and metal V of 1:0.3. Finally, orthorhombic Nb 18 V 4 O 55 Electrochromic film.
[0054] Example 4
[0055] The preparation method of Example 4 is the same as that of Example 1, except that the power of the metal vanadium target is adjusted to 92W, wherein the metal niobium target and the metal vanadium target are co-sputtered on the surface of the ITO quartz glass with a molar ratio of metal Nb and metal V of 1:0.35. 18 V 4 O 55 Electrochromic film.
[0056] Example 5
[0057] The preparation method of Example 5 is the same as that of Example 1, except that the power of the metal vanadium target is adjusted to 100W, wherein the metal niobium target and the metal vanadium target are co-sputtered on the surface of the ITO quartz glass with a molar ratio of metal Nb and metal V of 1:0.4. Finally, orthorhombic Nb 18 V 4 O 55 Electrochromic film.
[0058] Example 6
[0059] The preparation method of Example 6 is the same as that of Example 1, except that the power of the metal vanadium target is adjusted to 106W, wherein the metal niobium target and the metal vanadium target are co-sputtered on the surface of the ITO quartz glass with a molar ratio of metal Nb and metal V of 1:0.45. 18 V 4 O 55 Electrochromic film.
[0060] The orthorhombic Nb prepared in Examples 1-6 was characterized by X-ray diffraction (XRD). 18 V 4 O 55The crystal structure of the electrochromic film is characterized, and the crystal structure of the prepared electrochromic film can be determined by comparing the obtained XRD spectrum with the PDF standard card. XRD is a structural testing method, which is mainly used for phase analysis and material crystallinity determination. Its principle is that when a beam of X-rays is incident on a crystal, since the crystal is a structure composed of a large number of microscopic material units (atoms, ions, molecules, etc.) arranged in an orderly manner according to certain rules, the X-rays scattered by different crystal planes interfere with each other, and strong X-ray diffraction will be generated in certain special directions. According to the Bragg equation "2dsinθ=nλ", the angle and intensity of the diffraction line are closely related to the crystal structure. By analyzing the angle and intensity of the diffraction line, the lattice information of the material can be obtained.
[0061] Figure 1 The orthorhombic phase Nb prepared in Example 1-6 18 V 4 O 55 The XRD diffraction patterns of the electrochromic films are compared with the PDF standard card. According to the figure, the electrochromic films prepared in Examples 1-6 all have orthorhombic phase Nb 18 V 4 O 55 of the crystal structure.
[0062] Example 7
[0063] This example explores the orthorhombic phase Nb prepared in Example 1. 18 V 4 O 55 The optical modulation amplitude and dual-band regulation "warm state" adjustment mode of the electrochromic film are as follows:
[0064] The orthorhombic phase Nb prepared in Example 1 18 V 4 O 55 The electrochromic film was electrochemically tested in a glove box (water and oxygen content was less than 0.01) using a three-electrode system, where the electrolyte was 1 mol / L lithium perchlorate (LiClO 4 ) propylene carbonate (PC) solution, the counter electrode and reference electrode are lithium foil, and the working electrode is the orthorhombic Nb prepared in Example 1 18 V 4 O 55 The electrochromic film was subjected to electrochemical cycle testing by cyclic voltammetry (CV) with a voltage window of 1.25 V to 4 V and a scanning rate of 1 mV / s. At the same time, the full-band optical transmittance changes of the film during the electrochromic process were recorded in situ.
[0065] The in-situ optical transmittance is recorded by a spectrometer with a spectral range of 400nm-1600nm. The specific method is to place the sample in a 5×5×5cm cubic quartz electrolytic cell, the electrolytic cell is placed between a tungsten halogen lamp and a detector, the transmittance of the tungsten halogen lamp through the electrolytic cell filled with electrolyte is set to 100%, and the transmittance is set to 0% when the light source is completely blocked. During the test, the full spectrum (400nm-1600nm) and the single wavelength spectrum (550nm, 1100nm) are both measured in situ.
[0066] Figure 2 Orthorhombic Nb 18 V 4 O 55 The full-band optical transmittance change diagram of the electrochromic film at different voltages during the electrochromic process. According to the figure, the visible light transmittance of the film decreases slightly from the initial state to the coloring potential of 2.4V; there is an obvious regulation of the visible light band in the process from 2.4V to 2.0V; when it is lower than 2.0V, the film shows a sharp drop in full-band transmittance; the "warm state" mode appears at a coloring potential of 2.0V, at which time the visible light (550nm) transmittance and the near-infrared (1100nm) transmittance have a difference of more than 25%.
[0067] Figure 3 Orthorhombic Nb 18 V 4 O 55 The single-wavelength optical transmittance of the electrochromic film changes with time during the electrochromic process. According to the figure, there is an obvious sequence of modulation of visible light and near-infrared, and the visible light and near-infrared transmittance show the largest difference when the coloring potential is 2.0V. In general, the orthorhombic phase Nb 18 V 4 O 55 The electrochromic process of electrochromic film is divided into two stages. First, the transmittance of the visible light band decreases alone and presents a "warm state", and then the transmittance of the entire band decreases together until it is completely colored and presents a "dark state". 18 V 4 O 55 In this process, the electrochromic film achieved a large optical modulation amplitude of more than 70% for visible light and more than 85% for near-infrared light. This shows that the orthorhombic phase Nb 18 V 4 O 55 The electrochromic film uses only a single-component single-layer electrochromic material to achieve the "warm state" mode with the intrinsic properties of the material, and at the same time has a large optical modulation amplitude, providing a new option for dual-band electrochromism.
[0068] Example 8
[0069] This example explores the orthorhombic phase Nb prepared in Example 1. 18 V 4 O 55 The fast kinetic response characteristics of electrochromic films. The kinetics or response speed of electrochromic materials is an important parameter for evaluating the potential for commercial applications. At the same time, this parameter is also one of the goals pursued by researchers in this field. The in-situ spectra of the films recorded at different CV cycle scan rates are of great significance for discussing the kinetics of lithium ion injection and extraction. The modulation amplitude of the film at different scan rates clearly reflects the kinetic characteristics of the electrochromic film. The details are as follows:
[0070] Using the three-electrode system in Example 7, cyclic voltammetry was performed to measure the orthorhombic Nb 18 V 4 O 55 The electrochromic film was subjected to electrochemical cycle test with a voltage window of 1.25V to 4V. The film was cycled for 3 times at scanning speeds of 100mV / s, 50mV / s, 20mV / s, 10mV / s, 5mV / s and 1mV / s respectively. At the same time, the single-wavelength optical transmittance of the film at 550nm and 1100nm was recorded, representing the visible light band and near-infrared band, respectively.
[0071] Figure 4 is the orthorhombic phase Nb at different scanning rates 18 V 4 O 55 The single-wavelength optical transmittance change diagram of the electrochromic film shows that the optical modulation amplitude in the visible light band at a scanning rate of 1mV / s is 71.6%, and the optical modulation amplitude in the near-infrared band is 86.6%; at a higher scanning rate of 20mV / s, the optical modulation amplitude in the visible light band drops to 65.3%, and the optical modulation amplitude in the near-infrared band drops to 80.5%, but it can still maintain more than 90% of full coloration. Visible orthorhombic phase Nb 18 V 4 O 55 The electrochromic film can still maintain a sufficiently low colored state transmittance at a high scanning rate of 20 mV / s, and the time required for the cycle is only a quarter of that of 1 mV / s, which shows that the electrochromic film of the present invention has high coloring efficiency and fast response speed.
[0072] Example 9
[0073] This example explores the orthorhombic phase Nb prepared in Example 1. 18 V 4 O 55The high cycle stability of electrochromic films is also one of the important indicators for evaluating the performance of electrochromic films. The long-term stable operation of the film is the prerequisite for its transition from basic research to industrial production and application. The details are as follows:
[0074] The three-electrode system in Example 7 was used to conduct constant voltage to the orthorhombic Nb prepared in Example 1. 18 V 4 O 55 The electrochromic film was subjected to an electrochemical cycle test. This method enables the film to complete the injection and extraction of lithium ions in the shortest possible time and significantly shortens the time required for the experiment. Specifically, the constant voltage electrochemical cycle adopts a three-stage method. First, it is maintained at a voltage of 1.8V for 20 seconds, presenting a "warm state" mode; then it is maintained at a voltage of 1.2V for 30 seconds to make the film completely colored; finally, it is maintained at a high voltage of 3.5V for 30 seconds to make the film completely faded and present a "bright state". 18 V 4 O 55 The electrochromic film was subjected to 20,500 constant voltage electrochemical cycles, and the single-wavelength optical transmittance of the film was recorded at 550 nm and 1100 nm, representing the visible light band and near-infrared band, respectively.
[0075] Figure 5 It is orthorhombic phase Nb 18 V 4 O 55 The single-wavelength optical transmittance change graph of the electrochromic film undergoing a cyclic stability test shows that after 20,500 cycles of the cyclic test, the film can still maintain an optical transmittance equivalent to that of the initial state, but the optical modulation amplitude of the film decreases slightly, from 68% in the visible light band to 60%, and from 85% in the near-infrared band to 73%, with performance attenuation less than 15%. This indicates that the electrochromic film of the present invention has good cyclic stability and is expected to be used in large-scale commercial applications.
[0076] In summary, the orthorhombic phase Nb 18 V 4 O 55 The electrochromic film realizes the "warm state" mode by the intrinsic properties of the material, and has a large optical modulation amplitude, fast dynamic response characteristics and high cycle stability. These characteristics make it have the potential for commercial applications in smart windows, display devices and other fields.
[0077] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. An orthorhombic phase of Nb 18 V4O 55 Application of materials in electrochromic films.
2. An orthorhombic phase of Nb 18 V4O 55 The method for preparing an electrochromic film is characterized in that: Includes steps: The magnetron sputtering method is used to co-sputter metal Nb and metal V on the substrate surface to obtain amorphous Nb on the substrate surface. 18 V4O 55 film; For the amorphous Nb 18 V4O 55 The film was annealed to obtain orthorhombic Nb 18 V4O 55 Electrochromic film.
3. The orthorhombic Nb according to claim 2 18 V4O 55 The method for preparing an electrochromic film is characterized in that: In the magnetron sputtering method, a metal niobium target and a metal vanadium target are used to co-sputter metal Nb and metal V on the surface of a substrate, wherein the power supply power of the metal niobium target is 100W-200W, and the power supply power of the metal vanadium target is 25W-125W.
4. The orthorhombic Nb according to claim 3 18 V4O 55 The method for preparing an electrochromic film is characterized in that: The metal niobium target and the metal vanadium target co-sputter metal Nb and metal V on the substrate surface in a molar ratio of 1:0.2-0.
45.
5. The orthorhombic Nb according to claim 3 18 V4O 55 The method for preparing an electrochromic film is characterized in that: The distance between the center position of the surface of the metal niobium target and the metal vanadium target and the center position of the surface of the substrate is 120 mm to 150 mm.
6. The orthorhombic Nb according to claim 2 18 V4O 55 The method for preparing an electrochromic film is characterized in that: The working gases of the magnetron sputtering method are oxygen and argon, wherein the ratio of oxygen to argon is 5 sccm:45 sccm, and the gas pressure is 1Pa-1.5Pa.
7. The orthorhombic Nb according to claim 2 18 V4O 55 The method for preparing an electrochromic film is characterized in that: In the annealing treatment, the annealing temperature is 550° C. to 650° C., and the annealing time is 120 min to 300 min.
8. An orthorhombic phase of Nb 18 V4O 55 The electrochromic film is characterized in that The preparation is obtained by the preparation method according to any one of claims 2 to 7.
9. The orthorhombic Nb according to claim 8 18 V4O 55 The electrochromic film is characterized in that The orthorhombic phase Nb 18 V4O 55 The thickness of the electrochromic film is 300nm to 350nm.
10. An electrochromic device, characterized in that: The invention comprises a transparent conductive layer, an electrochromic layer, an electrolyte layer and an ion storage layer, wherein the electrochromic layer comprises the orthorhombic phase Nb as claimed in claim 8 18 V4O 55 Electrochromic film.
Citation Information
Patent Citations
Electrochromic device and preparation method thereof
CN109143714A
Thermal response dual-band electrochromic device
CN115398328A
Quick-response nickel oxide electrochromic film as well as preparation method and application thereof
CN115745418A
Visible-near infrared double-frequency electrochromic niobium tungsten oxide film and preparation method and application thereof
CN116119942A
Amorphous substrate VO2 single crystal film and preparation method thereof
CN117418202A
Cited By
Electrochromic intelligent window capable of accurately regulating and controlling mode as well as preparation method and application of electrochromic intelligent window
CN120010162A